Thermosensitive poly-((D,L)-lactide-co-glycolide)-block-poly(ethylene glycol)-block-poly-((D,L)-lactide-co-glycolide) hydrogels for multi-drug delivery - Cho, Hyunah (2014)
A current treatment strategy for peritoneal ovarian cancer is a combination of peritoneal surgery and multi-drug-based chemotherapy that often involves intraperitoneal (IP) injection. A thermosensitive poly-((D,L)-lactide-co-glycolide)-block-poly(ethylene glycol)-block-poly-((D,L)-lactide-co-glycolide) (PLGA-b-PEG-b-PLGA) hydrogel platform (thermogels) enabled gel loading of poorly work-soluble paclitaxel (cytotoxic agent), 17-allylamino-17-demethoxygeldanamycin (17-AAG, heat shock protein inhibitor), and rapamycin (mammalian target of rapamycin protein inhibitor). PLGA-b-PEG-b-PLGA thermogels (15%) carrying paclitaxel, 17-AAG, and rapamycin (named Triogel) made a successful transition from a free-flowing solution below ambient temperature to a gel depot at body temperature. Triogel gradually released paclitaxel, 17-AAG, and rapamycin at an equal release rate in response to the physical gel erosion. In an ES-2-luc ovarian cancer xenograft model, a single IP injection of Triogel (60, 60, and 30 mg/kg of paclitaxel, 17-AAG, and rapamycin, respectively) significantly reduced tumor burden and prolonged survival of ES-2-luc-bearing nude mice without notable systemic toxicity relative to those delivered by poly(ethylene glycol)-block-poly((D,L)-lactic acid) (PEG-b-PLA) micelles in solution via IP or intravenous (IV) injection route. These results show a great potential of a biodegradable thermogel platform carrying multi-drugs for IP chemotherapy in peritoneal ovarian cancer.